Pengembangan multimedia interaktif website dengan model Problem Based Learning pada Materi Hukum Pascal - Citra Leonie Citra Leonie; Indri Astuti; Haratua Tiur Maria (Institute of Computer Science (IOCS), 2023)
Pascal's Law is one of the materials students must master in learning science. 36% of students' learning outcomes on Pascal's law did not reach the KKM, namely 71. So, there is a need for efforts to increase understanding of Pascal's law concepts, one of which is to develop learning multimedia. This study aims to produce an interactive multimedia website with a problem based learning model on Pascal's law material. Using the Research and Development (R&D) method with the Dick, Carey, & Carey development model. This research and development resulted in the product